The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/ldrp.12239
|View full text |Cite
|
Sign up to set email alerts
|

Language‐Focused Interventions on Math Performance for English Learners: A Selective Meta‐Analysis of the Literature

Abstract: This meta‐analysis synthesized research on math performance outcomes for English learners (EL) as a function of language‐focused (math vocabulary) interventions. We included group and single‐subject design studies with children from kindergarten to 8th grade (3,766 students for group, 30 for single‐subject). Group studies yielded a mean Hedges’ g of 0.26 in favor of the interventions relative to the control conditions, whereas single‐subject studies yielded a mean Percentage of Non‐Overlapping Data of 81.01% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(221 reference statements)
0
6
0
Order By: Relevance
“…Based on prior research on effective word-problem interventions, the use of evidence-based strategies, such as those listed above, has been found to yield positive results in terms of improving word-problem outcomes for students with MD (Cook et al, 2020;Fuchs et al, 2014;Jitendra et al, 2015;Powell et al, 2019Powell et al, , 2021 as well as for emergent bilingual students who are still developing language proficiency (Arizmendi et al, 2021;Arsenault & Powell, 2022;Driver & Powell, 2017;Fuchs et al, 2021;Kong & Orosco, 2016;Orosco, 2014;Sanford et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior research on effective word-problem interventions, the use of evidence-based strategies, such as those listed above, has been found to yield positive results in terms of improving word-problem outcomes for students with MD (Cook et al, 2020;Fuchs et al, 2014;Jitendra et al, 2015;Powell et al, 2019Powell et al, , 2021 as well as for emergent bilingual students who are still developing language proficiency (Arizmendi et al, 2021;Arsenault & Powell, 2022;Driver & Powell, 2017;Fuchs et al, 2021;Kong & Orosco, 2016;Orosco, 2014;Sanford et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, culturally responsive math instruction is a framework for delivering and sustaining equitable and effective instruction for all students by integrating what we already know about effective math instruction for students with MD with culturally responsive instruction (see Figure 1; Utley et al, 2011). This framework is comprised of four key features (See Table 1): (a) using culturally and linguistically appropriate mathematic assessment tools and approaches (Arizmendi et al, 2021), (b) including antibiased contextual supports within math curriculum (Abdulrahim & Orosco, 2020; Driver & Powell, 2017), (c) providing linguistic supports (Driver & Powell, 2017), and (d) sustaining home-school collaborations (Abdulrahim & Orosco, 2020; Utley et al, 2011).…”
Section: Instructional Environmentsmentioning
confidence: 99%
“…To reduce language-processing load (Alt et al, 2014; Arizmendi et al, 2021), Mr. Cruz begins the lesson by reading the word problem aloud for the whole class while projecting the problem and pointing to each individual word while reading to assist with decoding, identifying, and defining words and assisting with the comprehension of the item (e.g., Hall et al, 2019). After reading the problem, he reminds the students once again.…”
Section: Instructional Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, interventions in these areas do not provide a complete account of difficulties in word problem‐solving performance. In fact, a recent meta‐analysis of Randomized Control Trial (RCT), studies (Arizmendi et al., 2021) focusing on vocabulary training in ELL children (see Kleemans & Segers, 2020, for rationale) found that such studies yielded low overall effect sizes (mean ES = 0.25, N = 3766) on math problem‐solving measures relative to control conditions. In addition, providing instruction in the children's first language (Spanish in this case) does not guarantee growth in math performance (see Miller, 2017, for review).…”
mentioning
confidence: 99%